THE IMPACT OF PROJECT-BASED LEARNING AND PROBLEM-BASED LEARNING ON WRITING SKILLS: A COMPARATIVE STUDY ON EXTROVERTED AND INTROVERTED INDONESIAN EFL STUDENTS - Prabowo, Jumbuh; Hartono, Rudi; Rukmini, Dwi; Saleh, Mursid (University of Kuningan, 2024)
This study aimed to investigate the effectiveness of Project-Based Learning (PjBL) and Problem-Based Learning (PBL) on enhancing the writing skills of students, considering their extroverted or introverted personality traits. The objective was to explore how different teaching strategies might yield varying results depending on the students' personalities. Employing a quasi-experimental design with a time-series approach, the research methodology included pre-and-post assessments, classroom observations, self-assessment tools for evaluating students' writing competencies, and questionnaires to determine their preferences. The research utilized three distinct forms of tests, revealing that the significance (Sig.) value stood at 0.005, which is below the 0.05 threshold for significance. This indicates a differential impact of PjBL and PBL on the writing abilities of introverted students. Conversely, for extroverted students, the significance value derived from the data was 0.300, exceeding the 0.05 level. This outcome suggests acceptance of the null hypothesis (Ho) and rejection of the alternative hypothesis (Ha), meaning there was no discernible difference in the effectiveness of the two strategies for extroverted students. Participants in the study were fourth-semester English Department students at the University of Sultan Ageng Tirtayasa (Untirta). The findings revealed that introverted students experienced variations in their writing skills when exposed to both PjBL and PBL, with these methods significantly influencing their writing abilities. In contrast, extroverted students did not show notable differences in their writing skills under the same teaching strategies, indicating that both PjBL and PBL were equally effective for them. This study underscores that the choice of teaching method can have varying impacts on the writing skills of students, particularly when considering their introverted or extroverted nature. It highlights that extroversion and introversion may play a role in how students respond to different educational approaches in the context of enhancing their writing skills.